Skeletal muscle phenotypic switching in heart failure with preserved ejection fraction - Saw, Eng Leng; Werner, Louis Dominic; Zamani, Payman; Chirinos, Julio A.; Valero-Muñoz, María; Sam, Flora (Frontiers in Cardiovascular Medicine, 2022)
Background: Skeletal muscle (SkM) phenotypic switching is associated with exercise intolerance in heart failure with preserved ejection fraction (HFpEF). Patients with HFpEF have decreased type-1 oxidative fibers and mitochondrial dysfunction, indicative of impaired oxidative capacity. The SAUNA (SAlty drinking water/Unilateral Nephrectomy/Aldosterone) mice are commonly used in HFpEF pre-clinical studies and demonstrate cardiac, lung, kidney, and white adipose tissue impairments. However, the SkM (specifically the oxidative-predominant, soleus muscle) has not been described in this preclinical HFpEF model. We sought to characterize the soleus skeletal muscle in the HFpEF SAUNA mice and investigate its translational potential. Methods: HFpEF was induced in mice by uninephrectomy, d-aldosterone or saline (Sham) infusion by osmotic pump implantation, and 1% NaCl drinking water was given for 4 weeks. Mice were euthanized, and the oxidative-predominant soleus muscle was collected. We examined fiber composition, fiber cross-sectional area, capillary density, and fibrosis. Molecular analyses were also performed. To investigate the clinical relevance of this model, the oxidative-predominant, vastus lateralis muscle from patients with HFpEF was biopsied and examined for molecular changes in mitochondrial oxidative phosphorylation, vasculature, fibrosis, and inflammation. Results: Histological analyses demonstrated a reduction in the abundance of oxidative fibers, type-2A fiber atrophy, decreased capillary density, and increased fibrotic area in the soleus muscle of HFpEF mice compared to Sham. Expression of targets of interest such as a reduction in mitochondrial oxidative-phosphorylation genes, increased VEGF-α and an elevated inflammatory response was also seen. The histological and molecular changes in HFpEF mice are consistent and comparable with changes seen in the oxidative-predominant SkM of patients with HFpEF. Conclusions: The HFpEF SAUNA model recapitulates the SkM phenotypic switching seen in HFpEF patients. This model is suitable and relevant to study SkM phenotypic switching in HFpEF.